2023
DOI: 10.3390/pathogens12030459
|View full text |Cite
|
Sign up to set email alerts
|

Combined Toxicity of the Most Common Indoor Aspergilli

Abstract: The most common Aspergilli isolated from indoor air samples from occupied buildings and a grain mill were extracted and analyzed for their combined (Flavi + Nigri, Versicolores + Nigri) cytotoxic, genotoxic and pro-inflammatory properties on human adenocarcinoma cells (A549) and monocytic leukemia cells induced in macrophages (THP-1 macrophages). Metabolite mixtures from the Aspergilli series Nigri increase the cytotoxic and genotoxic potency of Flavi extracts in A549 cells suggesting additive and/or synergist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Jakšić et al [ 12 ] presented a study on the cytotoxic, genotoxic, and pro-inflammatory properties of metabolite mixtures obtained from fungi on human adenocarcinoma cells (A549) and monocytic leukemia cells induced in macrophages (THP-1 macrophages). Metabolites of the most common Aspergillus species isolated from indoor air samples were used.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Jakšić et al [ 12 ] presented a study on the cytotoxic, genotoxic, and pro-inflammatory properties of metabolite mixtures obtained from fungi on human adenocarcinoma cells (A549) and monocytic leukemia cells induced in macrophages (THP-1 macrophages). Metabolites of the most common Aspergillus species isolated from indoor air samples were used.…”
mentioning
confidence: 99%
“…The contributors to this Special Issue provided insights into current issues in indoor mycology, particularly from a methodological [ 6 , 7 , 8 , 11 , 13 ], metabolic/toxicological [ 10 , 11 , 12 , 14 , 15 ], and taxonomical [ 8 , 9 , 13 , 16 , 17 ] point of view. Overall, two key messages emerge: (i) the current detection methods appear to be shifting from air sampling [ 11 , 12 ] to dust sampling [ 6 , 8 , 9 , 10 , 13 ], as the latter provides information on longer exposure periods and a higher biodiversity; (ii) the microbial composition of buildings is still largely unknown [ 9 , 13 , 16 , 17 ]. Our authors demonstrated that the indoor environment should also be a focus of taxonomical research, especially with regard to wooden and cellulosic materials [ 14 , 15 , 16 , 17 ], which proved to have a relatively high biodiversity.…”
mentioning
confidence: 99%
See 2 more Smart Citations